Unlocking Retail Success: A Comprehensive Exploration of Information and Communication Technology (Ict) Operations Practices in Nanostores - Ortega-Jiménez, Cesar H.; Sorto-Bueso, José R.; Amador-Matute, Andrea M.; Cruz-Amaya, Jennifer D.; Melgar-Martínez, Narciso A (LACCEI, 2024)
The integration of new information and communication technologies (ICT) plays a pivotal role in advancing Industry 4.0 within retail supply chains. However, the successful implementation of ICT in nanostores presents unique challenges. This study aims to identify and analyze key operational practices associated with ICT implementation in nanostores. Leveraging a combination of literature review, an academic expert panel, and surveys conducted with nanostores owners, the collected data underwent rigorous testing through Exploratory Factor Analysis. The empirical findings reveal three principal factors elucidating the obtained variance: Customer and Supplier Management, Operations Management, and Inventory Management. This not only aligns with existing literature but also offers contemporary quantitative insights for prioritizing ICT implementation in nanostores. The outcomes of this study serve as a valuable guide for academics, nanostores owners, and practitioners, facilitating informed decisions in ICT implementation and enabling proactive measures in implementation initiatives. In the landscape of the Internet of Things and the Fourth Industrial Revolution, the study highlights the significance of ICT implementation in nanostores, addressing a critical gap in the current scientific literature.